Pengembangan Aplikasi E-Order Service berbasis Website dengan memanfaatkan Payment Gateway (Studi Kasus : Hotel Lava View) - Irwan Kurniawan; Issa Arwani; Tibyani Tibyani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Lava View Hotel is a non-star hotel located in the Bromo Tengger Semeru tourist area, precisely in the East Java area, Probolinggo Regency. Hotel Lava View has not yet fully implemented standard health protocols (WTTC), one example is the use of unsterile menu books and used interchangeably by several customers as well as payment systems that do not require customers to make transactions digitally, which can trigger the spread of the corona virus. To support the health protocol policy, innovation is needed in the food ordering process, innovation that can be done by creating an ordering system via E-Order that will be used by Lava View Hotel customers so that the use of menu books is no longer needed, as well as a payment system that will be made automatically. online through a payment gateway that will be integrated with the food ordering website. This application was developed using the waterfall method for programming languages ​​using PHP and the codeigniter framework. The application development process starts from requirements analysis, system design, system implementation and system testing. The testing methods used are black box testing, compatibility testing, and usability testing. The test results on this application show that there is continuity with the system design and the application can run on several browsers.